Strategi Peningkatan Kinerja Pelayanan Publik Bidang Kepengurusan Izin Usaha Dan Izin Mendirikan Bangunan di Kantor Camat Lima Puluh Kabupaten Batu Bara - Achmad Fahry Siregar; Nina Siti S. Siregar; Maksum Syahri Lubis (Universitas Medan Area, 2022)
So the formulation of the problem is how is the performance of public services at the Lima Puluh Subdistrict Office of Batu Bara Regency along with strategies to improve the performance of these public services? And what are the obstacles to the performance of public services at the Lima Puluh Subdistrict Office of Batu Bara Regency? This type of research uses a descriptive qualitative approach. With data collection techniques in the form of interviews, documentation, and observation. The results of the study refer to the theory of Agus Dwiyanto (1995:45) namely output, efficiency, and effectiveness. So the output of service facilities at the Lima Puluh Subdistrict Office of Batu Bara Regency in terms of facilities and infrastructure to the community is not good enough. As well as the output in terms of services for managing business permits and building permits to the community has also not gone well. In terms of efficient service, the time for processing business permits and building permits has not been fully implemented to the community. This is because it is not in accordance with the Standard Operating Procedure (SOP). In terms of the effectiveness of the service of business licenses and building permits carried out at the Lima Puluh Subdistrict Office of Batu Bara Regency related to service terms and procedures, it can be said that it has not been effective.